MicroRNA-140-5p Mediates Renal Fibrosis Through TGF-β1/Smad Signaling Pathway by Directly Targeting TGFBR1 - Liao, Weitang; Liang, Peifen; Liu, Bo; Xu, Zhenjian; Zhang, Lili; Feng, Min; Tang, Ying; Xu, Anping (Frontiers in Physiology, 2020)
Renal tubulointerstitial fibrosis is usually the final outcome of various end-stage renal diseases. Recent studies have reported that microRNAs (miRNAs) play an important role in renal fibrosis. However, the biological function of microRNAs in renal fibrosis is complicated and remains unclear. In this study, our results show that miR-140-5p expression is significantly down-regulated in mice with unilateral ureteral obstruction and human proximal tubule epithelial cells (HK2) treated with TGF-β1. The knockdown of miR-140-5p upregulates the expression levels of collagen I, collagen IV, and α-SMA, decreases E-cadherin expression, and increases Smad-2/3 phosphorylation. In contrast, the overexpression of miR-140-5p decreases the expression levels of collagen I, collagen IV, and α-SMA, enhances E-cadherin expression, and inhibits the phosphorylation of Smad-2/3 in HK2 cells treated with TGF-β1. The dual-luciferase reporter assay revealed that TGFBR1 is a direct target gene of miR-140-5p. The enforced expression of miR-140-5p significantly inhibited the expression of TGFBR1 in HK2 cells. Furthermore, the knockdown of TGFBR1 has a similar effect of miR-140-5p overexpression on blocking the TGF-β1/smad signal pathway activation. In contrast, the overexpression of TGFBR1 reverses the effect of miR-140-5p inhibition on the activation of the TGF-β1/smad signal pathway. This study demonstrates that miR-140-5p regulates the TGF-β1/smad signaling pathway by suppressing the expression of TGFBR1. Therefore, miR-140-5p may have a therapeutic potential for preventing fibrotic kidney diseases through inhibiting the TGF-β1/Smad signaling pathway by directly targeting TGFBR1.